Improving the business processes management from the knowledge management (2016)
This paper proposes a model that integrates the knowledge management to the business processes management in order to improve the process performance. The proposal defines the knowledge management flow as an element that interacts with part workflows and provides rules and actions in the BPMN elements in order to improve the BPM. To achieve the aim, first, a survey was made in forty Colombian' companies in order to identify the state of the practice about business process management, knowledge management and their use through the workflows; then, different elements were identified and characterized in order to achieve the integration model proposed. This was experimented in forty business workflows of the companies analyzed. A use case shows how the interactions among model elements are, and how these can improve the process performance. This experience allowed to measuring the effect that the integration had in the business process management by means of a new metric that involve the knowledge management in the workflow. Finally, it was possible conclude that the knowledge management must be part to the BPM impacting directly the workflow, in order to improve the result offered to the organizational actors and customers.